Corporate Social Responsibility and Community Engagement: A Conceptual Review of Strategic Integration - Tomar, Lokesh; Seth, Salil (Journal of Emerging Management Studies, 2025)
Purpose - This paper explores how Corporate Social Responsibility (CSR) can move beyond philanthropic and compliance-based practices to become a driver of meaningful community engagement. It highlights the under-theorized relationship between CSR and community engagement, emphasizing the importance of participatory, localized, and culturally embedded approaches for sustainable socio-economic development. Design/methodology/approach - A review-based method was employed, synthesizing insights from recent scholarly literature and theoretical frameworks, including Carroll’s Pyramid of CSR, stakeholder theory, and legitimacy theory. The study integrated perspectives on social capital, sustainability, and inclusivity to assess how CSR practices are conceptualized and operationalized across contexts. Findings - The review demonstrates that while CSR is increasingly positioned as a strategic necessity, community engagement remains fragmented and often symbolic. The findings of the study reveal that the CSR models, which are rooted in Western perspectives, ignore the social and cultural conditions of developing economies, reducing their impact. Through the adoption of jointly developed inclusive strategies, firms can generate social value, promote trust, and develop sustained authority. Conclusion - The Research indicates that CSR initiatives generate stronger outcomes when they are purposefully coordinated with community engagement, surpassing communication to become deeply integrated practices. This coordination not only gives strength to stakeholder relationships but also promotes corporate adaptability and equality. Originality/value - The paper helps us to understand CSR by rethinking community engagement as a key element of CSR, bringing clarity to the concept, and identifying new ways for empirical research in developing economies. It raises doubts about existing ways of practicing CSR and provides a base for developing culturally responsive, participatory models that bridge the gap between theory and practice.